DAMPAK DAYA TARIK IKLAN DAN KOMENTAR PELANGGAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK PELANGGAN PADA PENGGUNA APLIKASI ONLINE SHOP DI KOTA MEDAN - Agung Anggoro, Muhammad; Purba, Mas Intan (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
The increasingly fierce competition of online shop products spurred online shop application providers to undertake business development strategy steps by strengthening digital business services and various service innovations to meet customer needs. This can be seen from the public interest in shopping at online stores because prices are more competitive, there is no need to bother coming directly to the store, and the goods purchased will be delivered to the buyers’ place. The population in this study that used mobile shop online application services was 100 respondents. The research data analysis method is quantitative descriptive statistical analysis and multiple regression analysis. The result of this research is that the attractiveness of advertisements and customer comments together have a positive and significant effect in increasing customer product purchasing decisions for users of online shop applications in Medan, while partially the attractiveness of advertising (X1) only has a positive and significant effect, but the variables customer comments (X2) have no positive effect in improving customer product purchasing decisions on users of online shop applications in the city of Medan.